IMPLEMENTASI METODE VLSM (VARIABLE LENGTH SUBNET MASK) PADA PEMETAAN IP ADDRESS LAN (LOCAL AREA NETWORK) DI LAB FAKULTAS SAINT DAN TEKNOLOGI (FST) UNISNU JEPARA - Teguh Tamrin; Nur Muhaidi; Anang Fathul Arifin; Ariyanto (Lembaga Pengembangan Kinerja Dosen, 2023)
Information technology is increasingly playing a role in supporting the efficiency and effectiveness of communication in modern organizations. Especially after the development of information technology which has an impact on the ease of communication. Computer networks can provide a communication medium for computer-based devices to exchange data and information. One of the computer networks is a Local Area Network (LAN). LAN is a computer network that includes computers that are connected to each other in one room or a building. Computer network settings can be done at the host level, by configuring the host addressing in it. Good host addressing will make it easier for computer network management so that it will optimize the performance of the computer network. One of the rules that can be used for addressing computer networks is the Variable Length Subnet Mask (VLSM). VLSM is a development of subnetting, which further optimizes the use of the subnet itself. Sometimes the subnet division still leaves host addressing, VLSM sees this deficiency and makes the remaining host addresses then set to form a new subnet. So it can be said that VLSM forms a subnet within a subnet. This study performs network addressing by subnetting and using VLSM to better manage the addresses of all hosts on the computer network. The results of the addressing made are expected to be implemented in the Faculty of Industrial Technology. This study does not calculate the bandwidth load obtained after the implementation of VLSM.